Correlation Between Serum 25 Hydroxy-vitamin D Levels and The Worst Pain Intensity in Postherpetic Neuralgia - Mellaratna, Wizar Putri; Jusuf, Nelva K; Yosi, Ariyati (UI Scholars Hub, 2022)
Background: Postherpetic neuralgia (PHN) is persistent pain in the affected dermatome that occurs more than three months after the eruption of the herpes zoster has disappeared. Vitamin D has a role in Schwann cell regeneration and stimulates the release of nerve growth factors. Methods: Blood sampling was performed to test serum 25(OH)D levels. Patients filled out their worst pain intensity using the Zoster Brief Pain Inventory questionnaire. The score was reported in Likert score (0-10), 0 indicating no pain and 10 indicating the most severe pain. Spearman correlation test was used, and p 0.05) and PHN durations (p >0.05). However, there were significant differences in serum 25(OH)D levels between sex groups (p Conclusion: No correlation exists between serum 25(OH)D levels and the worst pain intensity in PHN patients. Further research with a control group, liver function tests, and the duration of sun exposure data is needed to conclude the role of 25(OH)D in PHN patients.